Pengaruh Perubahan Tarif Terhadap Kepatuhan Wajib Pajak UMKM Sebelum Dan Sesudah PP No. 23 Tahun 2018 Di Kota Bandung (Studi Kasus Wajib Pajak UMKM Pada KPP Pratama Bojonagara Dan KPP Pratama Cibeunying) - Anjani Yulizar; Yeti Apriliawati (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
APBN funds in Indonesia come from three types of revenue sources. The biggest source is from tax revenue. The government issued a policy, namely PP No. 23 of 2018 at a rate of 0.5%. The government reduced the tax rate to 0.5% because the government predict that it would potentially increase the growth of taxpayers. On the other hand, it will decline the state cash receipts. This study aims to determine the effect of changes in tariffs on MSMEs taxpayer compliance. This type of research is quantitative comparative research. The population of this study is the Tax Office in Bandung. The sample using the purposive sampling method which is KPP Pratama Bojonagara and KPP Pratama Cibeunying. The data used in this study is secondary data in the form of tax revenue reports and taxpayer compliance for the years 2018-2019 obtained from KPP Pratama Bojonagara and KPP Prtama Cibeunying. The data analysis techniques used in this study are descriptive statistics, normality test, paired t-test, and wilcoxon sign rank test. The results of the study show that changes in tax rates have a significant effect on taxpayer compliance with the result of decreased revenues with an average value Rp1,112,510,309.06 and an increase in taxpayer compliancewith an average value of 757 taxpayers or 6.6%.